Programming the Stone Conservation Process - Learning from Ghesc Village/Italy - Artun, Ecenur (Eastern Mediterranean University, 2024)
The sustainable conservation of stone structures represents a complex challenge that necessitates the intelligent integration of both contemporary and traditional methodologies. The processes and strategies employed in the conservation and restoration of stone structures, as well as the roles and perspectives of various organizations involved in these efforts, are of critical importance for the effective execution and completion of projects, in addition to ensuring successful preservation. This thesis examines programming stone conservation through organizational and practical aspects of stone conservation in a case from Italy and establishes possible tools and practices in TRNC. It focuses on the restoration and conservation methods used, as well as the contributions made by different organizations and communities involved in the project. Through a comparative analysis of the conservation and restoration methods used in the Ghesc workshop and those applied to historic stone buildings within the TRNC, the thesis provides a critical examination of the necessary considerations for the implementation of various approaches and offers recommendations. In this context, the thesis emphasizes the importance of harmonizing modern and traditional approaches for the effective conservation of stone structures. Keywords: programming, stone conservation, Italy, TRNC

Taş yapıların sürdürülebilir korunması hem çağdaş hem de geleneksel metodolojilerin akıllıca bütünleştirilmesini gerektiren karmaşık bir zorluğu temsil eder. Taş yapıların korunması ve restorasyonunda kullanılan süreçler ve stratejiler ile bu çabalara dahil olan çeşitli kuruluşların rolleri ve bakış açıları, başarılı bir koruma sağlamanın yanı sıra projelerin etkili bir şekilde yürütülmesi ve tamamlanması için kritik öneme sahiptir. Bu tez, İtalya'dan bir vaka örneğinin taş korunmasının organizasyonel ve pratik programlanma aşamalarını inceler ve KKTC'de olası araçları ve uygulamaları belirler. Kullanılan restorasyon ve koruma yöntemlerine ve projeye dahil olan farklı kuruluşlar ve topluluklar tarafından yapılan katkılara odaklanır. Bu araştırma, zengin tarihi mirası ve kültürel önemiyle bilinen Kuzey Kıbrıs Türk Cumhuriyeti'ndeki yerel taş koruma ve restorasyon uygulamalarının potansiyel etkisini incelemektedir. Çalışma, Ghesc atölye çalışmasında kullanılan koruma ve restorasyon yöntemleri ile KKTC'deki yerel taş binalara uygulanan yöntemlerin karşılaştırmalı analizi yoluyla, çeşitli yaklaşımların uygulanması için gerekli hususların eleştirel bir incelemesini ve önerilerini sunar. Bu bağlamda, tez, taş yapıların etkin bir şekilde korunması için modern ve geleneksel yaklaşımların uyumlaştırılmasının önemini vurgulamaktadır. Anahtar Kelimeler: programlama, taş konservasyonu, İtalya, KKTC
Master of Science in Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2024. Supervisor: Prof. Dr. Kokan Grchev
Keywords: Thesis Tez; Architecture Department; Programming; stone conservation; Italy; TRNC; Conservation of stone structures; Building stone--Stone buildings--Conservation and restoration